Soil Fertility, Agronomic Performance, and Yield Response of Glutinous Corn to Black Soldier Fly Frass as Organic Fertilizer - Silin, Saturnino (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effects of Black Soldier Fly (BSF) frass, applied alone and in combination with inorganic fertilizers, on soil chemical properties, growth, yield, and economic returns of glutinous corn under upland conditions in Maddela, Quirino from February to May 2025. The experiment was organized in a Randomized Complete Block Design (RCBD) with six fertilizer treatments: full recommended NPK, reduced NPK, BSF frass alone, and combined applications of BSF frass with inorganic fertilizer. Agronomic parameters measured included plant height, ear length and diameter, biomass, yield, and cost and return analysis. The initial soil was very strongly acidic (pH 4.61) and deficient in organic matter and essential nutrients. Application of BSF frass improved soil fertility, increasing soil pH to 6.87 - 7.51, organic matter to 3.16 - 6.43 percent, total nitrogen to 0.16–0.32 percent, available phosphorus to 37.27 - 111.14 ppm, and potassium to 478.66 - 1044.70 ppm. Significant improvements in plant growth and yield components were observed across treatments. The tallest plants at harvest were recorded in the reduced NPK plus BSF frass treatment (136.33 cm), while the longest ears were obtained from the full NPK plus BSF frass treatment (15.53 cm). Biomass accumulation was highest in the integrated full NPK plus BSF frass treatment (351.72 g). The highest computed yield was achieved in full NPK plus BSF frass at 13.06 tons, followed by full NPK alone at 10.82 tons, whereas reduced NPK combined with BSF frass produced competitive yields of 10.29 tons.  Economic analysis showed that reduced NPK plus BSF frass generated the highest return on investment (305.21%), indicating improved profitability despite lower fertilizer input. Overall, BSF frass enhanced soil fertility, supported sustained crop growth, improved yield performance, and increased economic returns. The integration of BSF frass with reduced inorganic fertilizer rates is therefore recommended as a sustainable and cost-effective nutrient management strategy for glutinous corn production.
Keywords: Black soldier fly; Frass; Organic fertilizer; Soil fertility; Soil productivity